CHATGPT AS A DIGITAL MENTOR: A QUALITATIVE CASE STUDY OF CREATIVE WRITING DEVELOPMENT AMONG EFL UNIVERSITY STUDENTS IN INDONESIA - Muhammad Darma Febrian; Fiftinova Fiftinova (Esteem Journal of English Education Study Programme, 2026)
Despite the growing adoption of AI tools in higher education, limited studies have examined ChatGPT as a digital mentor in EFL creative writing within Indonesian higher education contexts. This study aims to examine how ChatGPT facilitates EFL creative writing development among Sriwijaya University students and to explore the challenges encountered. Employing a qualitative case study design, the research involved English Education students who completed an open-ended questionnaire, followed by semi-structured interviews. The collected data were analyzed using thematic analysis. The findings show that ChatGPT supported Creative Writing development in idea generation, structure quality, textual flow, and student confidence and motivation. However, challenges including overreliance, originality concerns, mismatched responses, and ambiguity were also identified. Theoretically, this study contributes to understanding AI-mediated constructivist learning in EFL contexts, emphasizing that ChatGPT's effectiveness as a digital mentor depends on critical and reflective student engagement. These findings have practical implications for integrating AI literacy and ethical considerations into EFL creative writing instruction.